KEPATUHAN WAJIB PAJAK KENDARAAN BERMOTOR DI CILACAP: DAMPAK APLIKASI SAKPOLE, KUALITAS PELAYANAN, DAN SANKSI PERPAJAKAN - Dewi Kusuma Wardani; Tri Wulandari (Jurnal Ilmiah Akuntansi Peradaban, 2023)
The purpose of this study was to determine the effect of service quality, taxation and Sakpole application on motor vehicle taxpayer compliance. Quantitative methods are used in research methods. Questionnaires were distributed to 90 respondents in Cilacap who are motor vehicle taxpayers using a Google form. Data were analyzed using IBM SPSS version 25, and convenience sampling was used as the sampling strategy. The conclusion of this study is that motor vehicle tax compliance in Cilacap is driven by tax sanctions. In contrast, taxpayer compliance in Cilacap is not affected by the quality of service or the application of Sakpole.